Piety in a Niqab : a Lens Held over the Women of İsmailağa Jammah - Fidan, Fatma Zehra, 1965- (Cambridge Scholars Publishing, 2019)
It is very likely that women's lives in black seem primitive, traditional, and subordinated to the researchers who observe them. However, in reality, the actors in such societies tell a different story, as this book shows. Women who wear the burqa build their identities on ideal resources, the Qur'an and sunnah, and in this way, achieve real peace and are privileged to easily pass religious examinations with the help of the sheik of their community. They have protective husbands who keep them from being contaminated by this dirty world, and homes that they manage with abundance. This approach.